A metaheuristic‐based data replica placement approach for data‐intensive IoT applications in the fog computing environment. (29th October 2021) - Taghizadeh, Jaber; Ghobaei‐Arani, Mostafa; Shahidinejad, Ali
Abstract: Over the past few years, Internet of Things (IoT) applications have grown rapidly. The data‐intensive IoT applications that take advantage of cloud servers for computations and data storage will result in higher latency and other network traffic in the Internet core. IoT applications are characterized by their sensitivity to latency. As an example, delays will result in irreparable damage in the medical and healthcare industries. Cloud servers are no longer necessary because cloud computing utilizes fog nodes that are closer to users. Nodes with different hardware capabilities pose a significant challenge since they differ significantly in latency and traffic reduction. This article presented a metaheuristic‐based method using the non‐dominated sorting genetic algorithm II for data‐intensive IoT applications in fog infrastructure. Besides, we provide a new automatic method for managing data replica transmissions, including deploying them in a fog cloud environment. The proposed solution was evaluated in the iFogSim simulator and compared with two other data replica placement methods in different scenarios. The results showed a decrease in latency and cost for data access and an increase in data availability.